The characteristic of features of legal representation in public law controversies arising from tax relations - Рябченко, Олена Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The article is devoted to the characteristic of features of legal representation in public law controversies arising from tax relations considering. The distinction in the legal personality of the plaintiff and the defendant representatives in the such controversies considering. The mandatory requirements for power of attorney, regardless of the status of the representation subject or entity with respect to representation is performed are grounded. Such requirements are serves to fix in the Code of administrative procedure of Ukraine. The necessity of the fixing at the legislative level of requirements of professionalism in respect of persons who carry out the representation of taxpayers in the administrative proceedings.